THE PARTICIPATION OF THE LOCAL ORTHODOX CHURCHES IN THE PREPARATORY PROCESS OF THE HOLY AND GREAT SYNOD – PREREQUISITE FOR THE RECEPTION OF ITS DECISIONS - IONIȚĂ, Viorel (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2017)
In this paper, the author emphasises the preparation, the proceedings and the reception process of the Holy and Great Council, that is one of the most complex radiographies of the Orthodox Church evolution out of a late Middle Ages to the present postmodern challenges. All these challenges have shown that the identity of the Orthodox Church is ensured through her faith transmitted through the Orthodox worship, which is the written expression of the Holy Tradition.